Is Deep Acting Prevalent in Socially Responsible Companies? The Effects of CSR Perception on Emotional Labor Strategies - Oh, Se Hyung; Hwang, Yein; Kim, Hwayoung (Frontiers in Psychology, 2019)
Drawing on social identity theory, this study examines the relationship between corporate social responsibility (CSR) perception and emotional labor strategies, and the effects of the interaction between CSR perception and moral identification on emotional labor strategies via affective organizational commitment. Our data from 352 frontline employees in the service industry show the main effect of CSR perception on emotional labor strategies. We find that CSR perception is positively (negatively) related to deep acting (surface acting). Affective organizational commitment mediates the relationship between CSR perception and surface acting but not between CSR perception and deep acting. Moral identification moderates the effects of CSR perception on surface acting through affective organizational commitment. This paper reveals that the employees’ views on their organization’s social responsiveness and morality affect their emotional labor strategies.